130k views
1 vote
Evaluate 3(x - 4) + 2x - x2 for x = 5.

User Doyin
by
5.7k points

2 Answers

4 votes
3(5-4) + 2(5)- (5)2
3(1) + 10 - 10
3+ 10 - 10
13 - 10= 3
User Gabriel M
by
5.3k points
3 votes

Answer:

= - 12

Explanation:

Given that:

= 3(x - 4) + 2x - x2

Now put x=5

= 3(5 - 4) + 2(5) - (5)^2

= 3(1) + 10 - 25

= 13 - 25

= - 12

i hope it will help you!

User Osynavets
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.